Determination of sulfur content in petroleum products – an overview. (4th July 2017) - Bajia, Subhash Chandra; Singh, Ram Janam; Bajia, Birbal; Kumar, Sudesh
ABSTRACT: Sulfur is invariably present in petroleum products, feedstock and crude oil. Several analytical methodologies are available to determine the sulfur content from trace level to percentage level. Analytical techniques being employed for sulfur determination in petroleum products, feedstock and crude oil are briefly described in this review article.